Original Forgiveness - Warren, Nicolas de, 1969- (Studies in phenomenology and existential philosophy., 2020)
"Rather than considering forgiveness exclusively in terms of an encounter between individuals or groups after injury, this book argues that availability for the possibility of forgiveness represents an original forgiveness, an indispensable condition for the prospect of human relations"--